Three functionally distinct classes of C-fiber nociceptors in primate - Wooten, Matthew (2014)
In primate C-fiber polymodal nociceptors are broadly classified into two groups based on mechanosensitivity. Here we demonstrate that mechanically-sensitive polymodal nociceptors that respond either quickly (QC) or slowly (SC) to a heat stimulus differ in responses to a mild burn, heat sensitization, conductive properties and chemosensitivity. Superficially applied capsaicin and intradermal injection of β-alanine, a MrgprD agonist, excite vigorously all QCs. Only 40% of SCs respond to β-alanine, and their response is only half that of QCs. Mechanically-insensitive C-fibers (C-MIAs) are β-alanine insensitive but vigorously respond to capsaicin and histamine with distinct discharge patterns. Calcium imaging reveals that β-alanine and histamine activate distinct populations of capsaicin responsive neurons in primate DRG. We suggest that histamine itch and capsaicin pain are peripherally encoded in C-MIAs and that primate polymodal nociceptive afferents form three functionally distinct subpopulations with β-alanine responsive QC fibers likely corresponding to murine MrgprD- expressing, non-peptidergic nociceptive afferents.